PEMANFAATAN MUSEUM BRI DAN MUSEUM JENDERAL SUDIRMAN SEBAGAI SUMBER BELAJAR IPS OLEH SISWA DAN GURU SD DI PURWOKERTO - Agung Nugroho; Lia Mareza (Khazanah Pendidikan, 2016)
Museum having the role and function of to use in the life of. Function museum unable to give spirit to develop the idea. Besides its function gather, identify, recording and next exhibiting. These functions explain a museum is not just exhibition dead , but also invited the historian , experts history, the community, teachers and students to have knowledge and get information value relics left by the history. This study was conducted in museum BRI and museum Jenderal Sudirman and including research qualitative. Technique data collection using interviews, observation and study documents. This study aims to analyze how the use of second this museum by teachers and primary school student. Keywords: museum, learning resources, social studies